Development Whitefly Pest Population (Bemisia tabaci G.) In Plants Cucumbers in the Pupuan Village, Tegallalang District, Gianyar Regency, Bali - I Wayan Dirgayana; Dicky Marsadi (Journal of Sustainable Development Science, 2023)
Cucumber ( Cucumis sativus Linn. ) is one plant lots of fresh vegetables consumed Indonesian society . Production your cucumber affected by the attack Whitefly pest ( Bemisia _ tabaci ). study This aim For know the presence of whitefly ( Bemisia tabaci ) on plants cucumbers in the Village Pupuan , District Tegallalang , Regency Gianyar . Study This held with observation or exploration in a way directly on the land plant cucumber . Study using 5 grid plots observation . In each plot, 5 clumps were observed plants , determination plant sample done with method diagonal sampling method . Total plants observed cucumber _ as sampling is 25 clusters plant . Observation held every a week very . Research result shows the Bemesia Pest tabaci are found in the field plant cucumbers at 14 Days After Plant with average number of nymphs 0.4 and imago 0.2 / Plant and Number population pest Bemesia tabaci on plants cucumber increase from observation I arrived _ observation to -VIII